ANALYSIS OF AMMONIA ASSIMILATION KINETICS AND DETERMINATION OF SUBSTRATE INHIBITION CONDITIONS IN VARIATIONS OF MOLASSES DOSE IN A BATCH REACTOR SYSTEM - Muhammad Iqbal Putra; Rizky Ibnufaatih Arvianto; Suhirman Suhirman; Adna Ivan Ardian; Denanda Clarasati Puteri; Dennis Farina Nury; Muhammad Zulfikar Luthfi; Maghfira Arum Lestari (Equilibrium Journal of Chemical Engineering, 2026)
The purpose of this study is to find the inhibitory phenomena caused by an excessive organic load and to estimate the ideal molasses dosage for ammonia assimilation by Saccharomyces spt. The experiment was carried out utilizing a batch reactor system with different molasses doses of 0, 5, 10, 15, and 20 mL at a constant starting ammonia content of 50 mg/L. Ammonia assimilation followed a pseudo-first-order model with a significant coefficient of determination R2 > 0.90 in the active dose range, according to the kinetic studies. The results confirmed that a dose of 10 mL was the optimum condition, producing the highest reaction rate constant (k) of 0.5107 day-1 and an ammonia reduction efficiency of 93.58%. On the other hand, raising dosage 20 mL caused a substrate inhibition phenomenon, which was marked by a drop in the k value to 0.2268 day-1 and a low ammonia reduction efficiency of 58.42% because of the initial acidification. The ammonia removal rate and biomass concentration (MLSS) had a very strong positive linear connection (r=0.98) according to Pearson correlation analysis, indicating that nitrogen assimilation with biomass growth-rather than physical volatilization-is the primary mechanism of removal. In order to optimize ammonia absorption performance without causing environmental toxicity, this study suggests a dose of 10 mL.